Arecoline and arecaidine lixiviation in areca nut blanching: Liquid chromatography‐ion trap‐time of flight hybrid mass spectrometry determination and kinetic modeling. Issue 11 (1st August 2022) - Liu, Xiaoling; Jiang, Lian; Zhang, Qi; Zhao, Zhendong; Zhang, Haide
Abstract: The characteristic alkaloids of areca (arecoline, guvacoline, arecaidine, and guvacine) are the primary toxic compounds that cause multiple health problems. Hence, estimating variations in areca alkaloids levels during areca processing is important, and the results may contribute to the reduction of the potential toxicity of chewing areca nut. In this study, a robust and accurate liquid chromatography‐ion trap‐time of flight mass spectrometry method was established for the simultaneous determination of four areca‐specific alkaloids and analysis of the two main toxic areca alkaloids (arecoline and arecaidine) during areca nut blanching. After the experimental data were fitted to an empirical model, high related coefficients indicated arecoline and arecaidine lixiviation during areca nut blanching followed second‐order kinetics. Then the kinetics parameters obtained were applied to a model for the prediction of the amounts of arecoline and arecaidine lixiviated during areca nut blanching in wide ranges of temperature and time. Novelty impact statement: A novel method was established for the simultaneous determination of four areca alkaloids. The leaching rates of arecoline and arecaidine during blanching followed second‐order kinetics. The results provide a prediction model for arecoline and arecaidine during areca nut blanching.